2016
DOI: 10.1080/19336918.2016.1182290
|View full text |Cite
|
Sign up to set email alerts
|

Probing cytoskeletal pre-stress and nuclear mechanics in endothelial cells with spatiotemporally controlled (de-)adhesion kinetics on micropatterned substrates

Abstract: The mechanical properties of living cells reflect their propensity to migrate and respond to external forces. Both cellular and nuclear stiffnesses are strongly influenced by the rigidity of the extracellular matrix (ECM) through reorganization of the cyto-and nucleoskeletal protein connections. Changes in this architectural continuum affect cell mechanics and underlie many pathological conditions. In this context, an accurate and combined quantification of the mechanical properties of both cells and nuclei ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Combining this approach with other micromanipulation tools revealed that tension in lateral stress fibers is gradually generated by anisotropic force contraction dipoles as the cell elongates and is strongly dependent on the cell spreading area . Similarly, the combination of the analysis of adhesion and de‐adhesion of endothelial cells on 2D patterns with different stiffness allowed the probing of nuclear mechanics without applying external forces and without any alteration of the nucleo‐cytoskeletal interactions such as those observed in micropipette aspiration experiments on isolated nuclei . Interestingly, differences in terms of regulation of the nuclear shapes on various rectangular 2D patterns were observed between fibroblasts and a model cancerous cell .…”
Section: Methods For Applying Force/deformation To the Nucleusmentioning
confidence: 96%
“…Combining this approach with other micromanipulation tools revealed that tension in lateral stress fibers is gradually generated by anisotropic force contraction dipoles as the cell elongates and is strongly dependent on the cell spreading area . Similarly, the combination of the analysis of adhesion and de‐adhesion of endothelial cells on 2D patterns with different stiffness allowed the probing of nuclear mechanics without applying external forces and without any alteration of the nucleo‐cytoskeletal interactions such as those observed in micropipette aspiration experiments on isolated nuclei . Interestingly, differences in terms of regulation of the nuclear shapes on various rectangular 2D patterns were observed between fibroblasts and a model cancerous cell .…”
Section: Methods For Applying Force/deformation To the Nucleusmentioning
confidence: 96%
“…MBs on the cellular membrane in the presence of magnetic field will stretch and mechanically activate the targeted membrane receptors. This technique is useful to study mechanotransduction as well as the rheological properties of cells . Different types of forces can be applied on membrane‐conjugated MBs ( Figure ): unidirectional tension delivered by the use of a permanent magnet (magnetic drag) or magnetic tweezers; torsional or rotational forces are applied by magnetic twisting/rotation.…”
Section: Particles As a Tool To Study Cells Mechanicsmentioning
confidence: 99%
“…Aside from studying internal biochemical pathways, MB‐assisted mechanical stimulation has been used to study the elastic and viscoelastic behavior of cytoplasm and nucleus for example, using spherical beads and microrods . When magnetic rods and wires are embedded in the cells and are subjected to a rotational magnetic field they behave as microrheometers.…”
Section: Particles As a Tool To Study Cells Mechanicsmentioning
confidence: 99%
“…Bearing in mind the role of PAWS1 in cell morphology, migration, cytoskeletal organization and focal adhesion distribution, we decided to examine its contribution to the architecture of cortactin and actin fibres. To this end, PAWS1 -/and control U2OS cells were plated onto fibronectin-coated crossbow and H-shaped (double-crossbow) micropatterns (Versaevel et al, 2016). We first noted that the lamellipodia of PAWS1 -/cells plated on the 'crossbow' fibronectin micropattern had a disorganized actin pattern ( Figure 3A; Supplementary Figure 4).…”
Section: Micropattern Analysis Of Cytoskeletal Actin Fibres and Cortamentioning
confidence: 99%